Presença americana na educação física brasileira : padrões culturais na imprensa periódica (1932-1950) - Assunção, Wallace Rocha (2012)
This research seeks to understand the circulation and appropriations of Americanism, a political and cultural movement that was born out of internal hegemony developed by the United States of America and becomes a model of modernity for other countries. Uses the repertoire of the New Cultural History and the evidentiary model based on Italian microhistoria as theoretical and methodologicalreference. As historic source, makes use of physical education periodicals that circulated in Brazil in the first half of the twentieth century.The analysis of the chosen documents indicates to us that from 1932, with the publication of the first periodicals on physical education,it is observable the circulation and appropriation of representations of Americanism, whose cultural traits permeates sports and school form of physical education. Moreover, the evidences points to a strategy for publicizing the American way of life, a synthesis of modernity and efficiency, especially in magazinesissued by commercial publishers that make more references to the United States than those edited by autarchic publishers, using the Pan-American movement to this sometimes and there is still the circulation of productsand goods advertising, produced by American industries. Furthermore we can see that even though it cannot be characterized as a locus for the dissemination of Americanism, the Young Men s Christian Associationhas contributed to the subsequent appropriation of this cultural movement, because it has been brought to South America by Americans who brought in their activities the images of American culture as the apex of modernity